High concentrations of cyanotoxins in reservoirs in the State of São Paulo (Brazil) may present a risk to public health - Moschini-Carlos, Viviane [UNESP] (2024)
Eutrophication and phytoplanktonic primary productivity are intensifying in continental aquatic ecosystems as a result of climate and land-use changes. Therefore, the proliferation of potentially toxic cyanobacteria is increasing in frequency, magnitude and duration, representing an ecological risk to ecosystems and human health. Our objective was to evaluate the water quality of ten subtropical reservoirs (Jaguari, Jacarei, Atibainha, Paiva Castro, Rio Grande, Guarapiranga, Barra Bonita, Bariri, Broa and Salto Grande), of the São Paulo region (Brazil), with an emphasis on cyanobacteria and cyanotoxins. From October 2021 to February 2022, we collected surface water samples to determine turbidity, chlorophyll-a, phycocyanin, microcystin and saxitoxin concentrations and phytoplankton biovolume. Water turbidity, chlorophyll-a and phycocyanin concentrations ranged from 2.0 to 24.6 NTU, 3.2 to 105.1 µg l–1, 12.4 to 445.1 µg l–1, respectively across reservoirs. Cyanobacteria was the most representative class in terms of biovolume, ranging from 0.086 ± 0.072 to 47.9 ± 5.3 mm3 l–1. Saxitoxins and microcystins were found in most reservoirs, with concentrations ranging from 0.016 µg–1 to 0.308 µg l–1, and from 0.107 to 200 µg l–1, respectively. According to the World Health Organization (WHO 2020) and the Brazilian legislation (Ordinance GM/MS n°. 888 of 2021), in the 10 reservoirs, saxitoxin concentrations are within the maximum permitted limits (3 µg l–1). However, total microcystin concentrations are above the maximum allowed value (1 µg l–1) according to the Brazilian legislation for most reservoirs. Considering all the information analyzed in relation to water quality and the community of cyanobacteria in the reservoirs, we can suggest that most of these environments present low water quality, which could present a risk to public health.